Efeito da polinização cruzada no número de sementes dos frutos de Ponkan Gold RBC - Krabbenborg, Danilo José (Universidade Federal de São Carlos, 2022)
Concerns about the production of table fruits such as Ponkan Gold RBC tangerine for many years were focused on effective pest and disease control in orchards. Over the years, the low number of seeds became a consumer demand. Thus, the objective of this work was to evaluate the influence of controlled cross-pollination on the number of seeds of the Ponkan Gold RBC (Royal Buds Citrus) variety. The experiment was carried out at the Citrograf Mudas farm in Mogi-Guaçu, on adult plants of the Ponkan Gold RBC variety from the orchard, which are planted outside a protected environment in one of the farm's plots. The experimental design was randomized blocks, with four replications. Eight treatments were adopted with different types of pollen. The viability test of these pollen grains was performed (in vitro pollen germination method). To extract the pollen grains, closed flower buds with 'swab' size were collected, they were kept in Petri dishes with filter paper and kept at 30ºC for 24 hours, for pollen grains to mature. When the Ponkan Gold RBC plants were in full bloom the treatments were installed. Evaluations were made of fruit set, number of seeds per fruit and physicochemical analysis of the fruits. Pollen viability and fruit set did not differ between varieties. The number of seeds in Ponkan Gold RBC tangerine fruits pollinated with Pêra orange pollen and Valencia orange had the highest number of seeds in relation to the other treatments. The treatment without hand pollination had the lowest number of seeds in relation to the other treatments. It is concluded with this work that there is a greater number of seeds in Ponkan Gold RBC fruits when pollinated with Pêra orange and Valencia orange, which shows the influence of cross-pollination in this fruit characteristic. For the commercial planting of the Ponkan Gold RBC variety, in order to obtain fruits with a low incidence of seeds, it is recommended to isolate the orchard by means of windbreaks or distance from varieties that increase the average number of seeds such as the Pêra and orange Valencia.
Effect of cross-pollination on the number of seeds of Ponkan Gold RBC fruits
Keywords: Citros; Autopolinização; Tangerina; Self-pollination; Tangerine; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA